Aspects Of Regional-Specific Characterization Of The Epidemiology And Risk Of Major Non-Communicable Diseases In The Adult Rural Population Of Andizhan (Texas Journal of Medical Science, 2026)
Major chronic non-communicable diseases (cardiovascular diseases, tumors, chronic respiratory diseases) have been among the most widespread diseases in the world for the past few years, and they remain the leading object of science and practice as the main cause of the therapeutic continuum among the population. Therefore, in the current era, preventive and prophylactic medicine, both theoretically and practically, and primarily in relation to major non-communicable diseases, has become an urgent issue and a necessity. According to the World Health Organization, "the annual mortality rate from them is 71%, and economic losses are about 1 trillion per year..." In the world, special attention is paid to epidemiological scientific research aimed at identifying the regional characteristics of the occurrence of major non-communicable diseases and creating and improving measures for the prevention of their various forms. In particular, the introduction of methods for early detection and prediction of the risk of developing major non-communicable diseases based on “…epidemiological markers” - risk factors, in populations with different characteristics is identified as one of the important tasks. At the same time, scientific research is also actively underway, including in Uzbekistan, to accurately and objectively assess the epidemiological and clinical processes in non-communicable diseases, to improve predictive algorithms - models, taking into account the territorial course of diseases and the “accumulation of risk factors”. However, despite the great achievements of medical science, there is no generally accepted methodology for the prevention of major non-communicable diseases. Western medicine believes that the outcome of prevention (population health) is 50% related to living conditions and lifestyle, 20% to environmental conditions, 20% to genetic factors, and 10% to the healthcare system. Eastern medicine believes that the outcome of prevention is 70% related to thinking, 20% to lifestyle, and 10% to nutrition.